Assessment of Consolidation Behavior for Stabilized Peat Using Cement and Ceramic Dust - ZAIDAN, MOHD NAZRI; ZAINORABIDIN, ADNAN (Recent Trends in Civil Engineering and Built Environment, 2022)
Peat known as the most problematic soil and peat also categories as an organic complex soil. Problematic peat cause by high void ratio, poor stability and high compressibility. This study to determine settlement behavior of treated peat with consolidation test for long term settlement and relate laboratory data with field data. Stabilizer will be used in this study cement and ceramic dust. Amount percentage of stabilizer that used for sample is 4% and 8% for both type of stabilizer. Sieved peat passing 2.36mm for mixed with stabilizer and standard odometer test based on BS 1377 used in this study. The consolidation test will determine the settlement of sample for every interval time that has been set for data recorded. The data will be analysis by plotting graph to determine Compression index, Coefficient of Consolidation and Secondary Compression index. From the analysis data it is show significant change due the peat has been treat with stabilizer and it is influenced by the total percentage of stabilizer used in the mixture. The analysis obtained will be compared with untreated peat to determine differentiation of treated and untreated of peat. For further research, laboratory tests for fundamental properties of stabilizer agents used to treat problematic soil, such as liquid limit tests, specific gravity, and other tests related to basic properties, may be conducted. From here, researchers may learn more about how stabilizers might enhance problematic soil and evaluate if a stabilizer is acceptable and appropriate for a certain soil condition.